The essential cookie companion. (The Countryman Press, a division of W.W. Norton & Company, Independent Publishers Since 1923, 2021)
"With gorgeous new photography, King Arthur's foolproof recipes and clear, encouraging directions empower bakers to make beautifully delicious cookies. From the perfect chocolate chip cookie (whether you prefer it chewy, crisp, or in-between) to simple sugar cookies ranging in flavor from lemon to cinnamon to vanilla, from brownies and blondies to shortbread, graham crackers, macaroons, chocolate biscotti-you'll discover more than 400 delightful cookies in these pages. From classic flavors to modern techniques, these recipes will inspire and satisfy cookie lovers and bakers at every skill level. King Arthur Baking Company's talented and trusted test kitchen experts provide an overview of essential cookie ingredients-updated and revised-along with step-by-step instructions and illustrations that result in visually impressive and incredible-tasting cookies. Recipes are enhanced with sidebars full of hints, shortcuts, troubleshooting advice, and recipe lore. With tips on substitutions and variations; information about gluten-free flours; details on measuring and weighing ingredients; instructions for making icings, fillings, and dips; and even advice on high-altitude baking, this truly is the ultimate cookie cookbook"--